2017
DOI: 10.20319/pijss.2017.32.20962108
|View full text |Cite
|
Sign up to set email alerts
|

Hurdle Race in Early Education – 10 Weeks of Arts and Physical Activities

Abstract: Research objectives. Hurdling (in sport = hurdle run, in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 7 publications
2
2
0
Order By: Relevance
“…Similar conclusions were drawn by Iskra [26] by examining the correlation between the sports level of 400-metres hurdles and the size of training loads. He showed that the previously mentioned training means are characterized by a lack or a very small dependence of the final result for the 400-metres hurdles at a selected stage of the annual cycle.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Similar conclusions were drawn by Iskra [26] by examining the correlation between the sports level of 400-metres hurdles and the size of training loads. He showed that the previously mentioned training means are characterized by a lack or a very small dependence of the final result for the 400-metres hurdles at a selected stage of the annual cycle.…”
Section: Discussionsupporting
confidence: 84%
“…The eliminated training means included: technical and speed exercises, pace runs, general strength of lower limbs, directed strength of lower limbs, technical exercises – running pace, and runs over 4-7 hurdles (Table 1). All these training means belong to the “target” groups [26]. The results of the analysis confirm the views of researchers of competitive sports, claiming that in highly qualified training these exercises should be limited and the focus should be placed on special training.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…The pace distribution over this distance depends mainly on the special endurance predispositions (Hanon and Thomas, 2011;Iskra et al, 2017;Vazel, 2011), directly related to anaerobic changes and blood lactate concentrations (Gefen et al, 2002). In terms of training theory, special endurance describes efforts with a submaximal and maximum intensity in 90-98% of the runner's abilities and running sections from 300 to 600 m with optimal rest periods (Gorostiaga et al, 2010;Iskra et al, 2016). The application of the training load depends mainly on the period of the annual training cycle (Warden and Britain, 1988).…”
Section: Introductionmentioning
confidence: 99%